Community responses to flood risk management – An empirical Investigation of the Marine Protected Areas (MPAs) in Malaysia - Masud, Muhammad Mehedi; Sackor, Ahmad S.; Ferdous Alam, A.S.A.; Al-Amin, Abul Quasem; Abdul Ghani, Ahmad Bashawir (Elsevier Ltd., 2018)
The vulnerability of the Marine Protected Areas (MPAs) to flood disasters affects not only the underlying eco-centric and anthropocentric values therein, but also the coastal communities that are adjacent to the MPAs. The consequences can lead to economic, social and environmental degradation. As such, the perception of the coastal communities about flood risk occurrences and their effects on the MPAs are crucial for Flood Risk Management (FRM) exercises. Having an insight into the perceptions of the coastal communities about the build-up of flood risk analysis adds robustness to the FRM cycle as it can increase levels of preparedness, responses and recoveries. This paper examines the relationship between the communities’ perceived vulnerability, perceived severity of flood risks, perceived benefits of flood risk management, perceived barriers of flood management and their previous experience of flood risk management. The paper seeks to understand how this intersection influences the human intention to participate in the preventive and precautionary measures related to flood risks in MPAs. To achieve the objectives, a survey questionnaire was conducted on a sample of 320 households from MPAs in Malaysia. Data were analysed using the structural equation modelling (SEM). This study revealed that perceived susceptibility, perceived severity, perceived benefits, and previous flood risk experience have a positive and significant influence on the intention to participate in prevention activities. This study offers valuable insights that may be useful for policymakers in promoting greater public engagement in managing climatic disasters including potential flood risks in MPAs.